O diálogo entre a formação tecnocientífica e a humanística na educação tecnológica: uma problematização a partir do estudo de caso do curso superior de Tecnologia em Gestão Ambiental da UFSM - Ilha, Gisandro Cunha (2014)
Technological Education had a significant increase in its quantitative courses and offered vacancies in recent years, especially after the establishment of REUNI, the reconstituting of the former Federal Centers of Technological Education (CEFET's) and the implementation of the Federal Institutes of Education, Science and Technology (IFET's). However, many issues related to the educational process of future technologists need to be reexamined. This paper, based on the case study of the Technology Course in Environmental Management (CSTGA) from UFSM, intends to: determine whether, in CSTGA, there is a dialogue between scientific-technical training and the humanistic training; examine according to the theoretical framework of this study - Freire / STS - the elements involved in the articulation or non-articulation between the techno-scientific and humanistic training, as well as to discuss possible implications to the training process, based on the verification of this study. As a methodological approach we use the Text Analysis Discourse, the corpus of analysis were the Pedagogical Project of the Course, the questionnaire answered by the students and the semi-structured interview with the teachers of the course. From this corpus of analysis meaning units emerge which bring forward categories, from which it is discussed the specific situation of the studied course. The results of this analysis point in the direction of non-articulation between techno-scientific and humanistic formation, with possible causes related to the teacher training, the curriculum inflexibility and the presumption on the part of the academic community that these courses are guided, almost exclusively, by the demands the labor market.